The Effects of Telecommunication Service Quality Dimensions on Customer Satisfaction in Kathmandu Valley - Sah, Gunja Kumari; Pokharel, Shiva Prasad (Journal of Nepalese Business Studies, 2021)
Telecommunications have become a vital tool for the success of any business. The 21st-century telecommunication business has been described by hi-tech competition, which has brought attention to customer satisfaction. The study aimed to identify major influential dimensions that affect customer satisfaction. It was accompanied by a descriptive and causal research design and used a structured questionnaire as a survey instrument of the service quality (SERVQUAL) model. The population of this research covered all customers of the Telecommunication industry located at Kathmandu valley, and the sample considered 400 customers through convenience sampling techniques. The survey questionnaire was set in three sections with 38 questions of various types to collect data. The result showed a noteworthy strong positive relationship between service quality dimensions and customer satisfaction. It also revealed security was the major influential dimension of customer satisfaction, followed by tangibles, assurance, and empathy. The finding of the study helps all telecommunication industries to enhance service quality and develop a strategy to increase customer satisfaction and value. Hence, it infers that security, tangibles, assurance, and empathy increase the customer's satisfaction in telecommunications services. Overall service quality dimensions are commonly considered as crucial features of customer satisfaction.